Iowa RBA, September 7, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Iowa RBA for September 7, 1998. Highlights include Burrowing Owl, White-winged Scoter, and Red-necked Phalarope. Includes notes for updates for September 8, September 9, and September 11. Epson - sheet feed/flatbed